서산시 농업·농어촌 발전계획 수립 연구 〔2006～2015〕 - 유승우 (한국농촌경제연구원, 2006)
Ⅰ. Objective The objective of this study is to establish a long-term regional development plan for agricultural and rural sectors in the city of Seosan, which is located in the western part of Chungnam Province. For this purpose, this study was carried out to review the city's regional, environmental and social-economic characteristics under the current situations both inside and outside the city and evaluate the city's potential capacities. Ⅱ. Methodologies For carrying out this study, we used various methodologies such as field survey, questionnaire survey, consumer survey, overseas case study, and literature research. In the field survey, we investigated both the demand for development and natural resources in Seosan through regional workshops at the administrative districts of "eup" and "myeon." We also interviewed agricultural policy makers, city circle members, and producers to review the demand for agricultural investment and finance in Seosan. A questionnaire survey carried questions on the demand for development and the priorities for agricultural investment and finance. In the literature research, we carried out a referential study on regional development and the city of Seosan. We also examined the green tourism and environment-friendly agricultural development in Koyto and Nara prefectures in Japan. Ⅲ. Findings This study suggested development strategies for each one of the four regions, which were classified by agricultural and rural characteristics of Seosan. They are 1) northern semi-plain region, 2) central semi-plain region, 3) southwestern plain region, and 4) southeastern semi-plain region. The northern semi-plain region, which includes Daesan-eup and Jigok-myeon, needs to create an environment-friendly agricultural area and build up "farm-experience" and "rural-information" villages. The specialized products for this region are rice, tomato, pumpkin, and sweet potato. For the central semi-plain region, which covers Seongyeon-myeon and Eumam-myeon, the study suggested a plan to develop a suburban/agricultural area and create a specialized cultivation area for wild rocamboles to increase farm income. For the southwestern plain region, which consists of Inji-myeon, Buseok-myeon and Palbong-myeon, Seosan City should create a Seosan "bio well-being specialized complex" and main producing areas of garlic, ginger, orchids, and lilies. Seosan City also needs to construct a traditional rural theme village to promote rural-urban exchanges and increase farm income by utilizing the unique cultural resources of Seosan. It is also necessary to build an agricultural processing complex (APC) linked to the West Coast Highway. For the southeastern semi-plain region, which consists of Unsan-myeon, Haemi-myeon, and Gobuk-myeon, Seosan City needs to create a branch of "National Tree Garden" in Hwangrak Valley as part of its plan to construct a central point for rural-suburban exchanges. It should expand related programs and facilities, which link existing resources within the city to the theme of rural life. In addition, it should create a software program which informs sightseeing routes to historical and cultural sites within the city. Also, Seosan City needs to construct an organic livestock complex in Unsan-myeon and expand the support for the organic cultivation of ginseng for raising the farmers' income. In this study, we suggested 44 new strategic projects such as the construction of an APC, sewage treatment facilities, and a green rural-experience village in addition to the creation of environment-friendly agricultural areas and parks. The total amount of investment for these projects will be at 121.7 billion won for the period 2006-2015. Researchers: Seung-Woo Ryu, Shi-Hyun Park, Duk Huh, Byung-Ryul Kim, Soo-Suk Kim, Kyong-Cheol Park, Jung-Hyun Kang, Cheol-Ho Kim, Uhn-Soon Gim E-mail address: sewryu@krei.re.kr Research period: 2005.9 - 2006.10